RUSSIA-CHINA PARTNERSHIP: AFTERMATH CONSEQUENCES OF THE UKRAINE CRISIS - Muttaqien, Audi Izzat; Alimuddin, Sitti Zarina Binti; Hayatunufus, Hayatunufus; Al-Fadhat, Faris (JWP (Jurnal Wacana Politik), 2024)
This research examines the Russia-China alliance after Russia invaded Ukraine in February 2022, which impacted the world and led to polarity in international politics. The United States and its western allies have tried to weaken Russia’s dominance economically and politically. At the same time, China has supported and strengthened cooperation with Russia. This study uses a qualitative method by analyzing and critically reading the data collected through literature study. The result found that the expansion of NATO membership triggers Russia to act because of external threats. The West agreed to embargoes and sanctions against Russia, affecting 90% of Russian oil and gas markets. However, Russia showed its strength and warned of nuclear threats. This study also contends that amid the US pressure that caused Russia to lose its Western buyers, China backed Russia and became its potential oil buyer. The US pressure on Russia has brought Russia-China even closer.